How Alluvial Storage Controls Spatiotemporal Water Balance Partitioning in Intermittent and Ephemeral Stream Systems - E. Zarate; M. S. Andersen; G. C. Rau; R. I. Acworth; H. Rutlidge; A. M. MacDonald; M. O. Cuthbert (Water Resources Research)
Abstract The hydrological dynamics of intermittent rivers and ephemeral streams (IRES) impacts the availability of water to riparian ecosystems, the height of downstream runoff peaks, and the replenishment of groundwater systems. Despite its significance, the influence of superficial geology on IRES flow processes remains an area of limited understanding. Here we first present a comprehensive data set encompassing streamflow and groundwater levels from an intermittent stream situated in New South Wales, Australia. We then use targeted geophysical investigations to show how the configurations of superficial geology control the streamflow and groundwater responses. The analysis reveals that periods of stable stream stage consistently occur after episodic surges in streamflow, followed by recession and channel desiccation. The duration of the stable phases exhibits an upstream‐to‐downstream pattern, reaching a maximum of 44 ± 3 days upstream and then abruptly declining further downstream. There is remarkable consistency in the duration of these stable flow periods, irrespective of the size of preceding streamflow peaks. We propose two primary controls of this behavior: (a) variability in permeability contrasts between channel alluvium and surrounding geological deposits, and (b) longitudinal fluctuations in the volume of the recent channel alluvial reservoir. The interplay of these controls generates a “goldilocks zone,” which optimizes riparian water availability and the potential for groundwater recharge in IRES landscapes. These geological controls may reflect a continuum present in other dryland catchments with widespread implications for groundwater recharge and stream classification based on flow occurrence and duration.